Geochemical characteristics and significance of heteroatom compounds in lacustrine oils of the Dongpu Depression (Bohai Bay Basin, China) by negative-ion Fourier transform ion cyclotron resonance mass spectrometry. (November 2018) - Ji, Hong; Li, Sumei; Greenwood, Paul; Zhang, Hongan; Pang, Xionqi; Xu, Tianwu; He, Nannan; Shi, Quan
Abstract: Saline and freshwater lacustrine oils from the Dongpu Depression (Bohai Bay Basin) were characterized by negative-ion electrospray ionization (ESI) Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS). ESI-FT-ICR MS detected a large range of nitrogen and oxygen compounds in the oils, mostly comprising N1, O1, O2 and N1 O1 species. The low mature oils are dominated by O1 species with double bond equivalent of 4 (DBE = 4; mainly alkylphenols), O2 species with DBE = 5–6 (i.e., hopanoid, secohopanoic and steroid acids) and DBE = 1 (i.e., fatty acids), indicating a genetic relationship between oxygen compounds and their precursors. The nitrogen and oxygen compounds were significantly influenced by maturity, with the lower maturity oils analyzed enriched in O2 species, particularly fatty acids and 4–5 ring naphthenes with biologically sourced hydrocarbon skeletons: ratios of O2 /N1  > 0.7; C20–30 /C15–45 -DBE1 -O2  > 0.4; and DBE5–6 /DBE12–22 -O2  > 6.0 may be useful indicators of low maturity. With increasing maturity, the condensation degree of the compounds increased and the carbon number decreased. The relative abundances of N1 and O1 species with the following specific DBE carbon number ranges were particularly sensitive to maturity: DBE9–12 /DBE15–18 -N1, C20–28 /C29–40 -DBE12 -N1, C20–30 /C31–50 -DBE15 -N1, DBE9–12 /DBE4–20 -O1 and C20–30 /C31–50 -DBE8 -O1 . In some instances the FT-ICR MS proxies provided a more reliable indication of high maturity levels than traditional sterane based maturity parameters. However, several of these species were also responsive to other influences, namely C20–28 /C29–40 -DBE12 -N1 and C20–30 /C31–50 -DBE15 -N1 ratios reflected an organofacies control and DBE9–12 /DBE4–20 -O1 and C20–30 /C31–50 -DBE8 -O1 ratios changed with thermochemical sulfate reduction (TSR)– confirmed by δ 34 S variances of OSCs. In light of the multiple controls on the nitrogen and oxygen compounds, DBE9–12 /DBE15–18 -N1 ratio seems unaffected by organofacies or TSR and was considered the most reliable maturity proxy displaying a similar or better maturity relationship than Ts/(Ts + Tm). Aside from secondary alteration effects, the freshwater samples showed several compositional differences to the saline samples, albeit from a limited data set, including generally higher O2 and N1 (particularly low MW) product abundances, lower abundances and quite different distribution of O1 products. These distinctions suggest ESI FT-ICR MS analysis has potential for distinguishing these sample types. Highlights: Heteroatom compounds in saline lacustrine oils were detected. Abundant O and N compounds were identified in low mature oils. Parameters of N and O compounds indicating maturity were proposed. NSO compounds in several saline lacustrine oils were probably impacted by TSR.